2021
DOI: 10.36740/wlek202103113
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depressive Disorders in Patients With Arterial Hypertension

Abstract: The aim: To study the influence of anxiety and depressive disorders on life quality of patients with arterial hypertension. Materials and methods: 55 patients with arterial hypertension (AH) of 2nd stage were examined to reach the goal. Age diapason was 25-73 years, the middle age was 53.56+10.28. There were 58.2% (32) of women and 41.8% (23) of men among the patients. Results: Results analysis of the investigation of patients with arterial hypertension and anxiety and depressive disorders using the Spielberg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…For this reason, the present work aims to (a) investigate the trajectories of Hr-QoL and SWB over time to better clarify their trend over patients with hypertension and MetS and (b) investigate psychological and personality variables (LoC, self-esteem, trait anxiety, Type A and Type D traits) significantly affecting the longitudinal changes over time in Hr-QoL and SWB. We expect that patients will perceive better well-being and quality of life due to the monitoring of their BP, as we can see in previous work [ 39 ], and that the above-mentioned psychological and personality traits will significantly predict this trend; in particular, we expect an impact of self-esteem and internal LoC [ 24 , 26 ], as well as an influence of Type A, Type D behaviors [ 35 , 36 , 37 ] and trait anxiety [ 31 , 32 ] on both mean outcomes (Hr-QoL and SWB) according to previous studies.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…For this reason, the present work aims to (a) investigate the trajectories of Hr-QoL and SWB over time to better clarify their trend over patients with hypertension and MetS and (b) investigate psychological and personality variables (LoC, self-esteem, trait anxiety, Type A and Type D traits) significantly affecting the longitudinal changes over time in Hr-QoL and SWB. We expect that patients will perceive better well-being and quality of life due to the monitoring of their BP, as we can see in previous work [ 39 ], and that the above-mentioned psychological and personality traits will significantly predict this trend; in particular, we expect an impact of self-esteem and internal LoC [ 24 , 26 ], as well as an influence of Type A, Type D behaviors [ 35 , 36 , 37 ] and trait anxiety [ 31 , 32 ] on both mean outcomes (Hr-QoL and SWB) according to previous studies.…”
Section: Introductionmentioning
confidence: 58%
“…Trait anxiety refers to the individual differences in anxiety-proneness as a personality trait, so persons with higher trait anxiety are more strongly disposed to manifest anxiety state [ 30 ]. In this field, many studies reported high levels of trait anxiety in patients with hypertension [ 31 ]; furthermore, trait anxiety has been associated with poorer Hr-QoL [ 31 ] and lower levels of SWB [ 32 ] in patients with hypertension compared to the general population. However, the causal effect between these pathological conditions and the well-being sphere remains unclear and needs further clarification [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of various complications and long-term effects of medication, patients with hypertension are often accompanied by depression. 22 , 23 Given the potential impact of long-term complications, reduced quality of life, and impaired self-management of hypertension among individuals with OSA, comorbid hypertension, and depression, it is crucial to emphasize the importance of prognostic evaluation for this population.Additionally, a high AHI has been prevalent in hypertensive patients, 24 which may contribute to a poor prognosis in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological complications are common in cardiac-cerebral vascular disease patients ( 13 , 14 , 19 ). It has been reported that anxiety, depression, and cognitive impairment rates can range from 20.4 to 39.2%, 26.2 to 31.2%, and 18.6 to 43.2%, respectively, among AIS patients ( 15 , 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%